Utilization of Visual Media in Thematic Learning in Elementary Schools - Aji Wasito; Ali Imron Al ma'ruf; Djalal fuadi; Laili Etika Rahmawati; Endang fauziati (Universitas Pendidikan Ganesha, 2022)
During the learning process students do not participate and do not study well. Teachers need better learning with steps to increase motivation. Visual media can be a solution to increase student motivation. The aim of this study is to analyses the use of visual media in learning thematic in grade VI along with the obstacles and solutions done by the teacher. The subjects of this study were students, teachers and principals of elementary school. This method uses descriptive qualitative method. Data collection techniques in this study use the form of observation, interviews and documentation. The validity test of the data used is technique triangulation and source triangulation. The research shows that the use of visual media in thematic learning in class VI consists of planning, implementation and evaluation. The obstacle that faced by teachers during the process of using visual media in thematic learning, namely learning media is incomplete or limited , lack of participation of parents and students which not enough understand theory which be delivered by teacher. The solution to overcome the problem of using visual media in thematic learning is to create interactive and attractive teaching materials and build communication between teachers and students.